Hybrid Learning Management as a Strategy to Improve Learning Motivation in Higher Education - Hasanah, Mila (JURNAL AL-TANZIM, 2022)
Learning motivation for students in higher education has a vital role in making learning effective, especially during the covid 19 pandemic. This study aims to understand the implementation of hybrid learning management in improving student learning motivation in the Madrasah Ibtidaiyah Teacher Education Departement, at the Tarbiyah and Teacher Training Faculty, UIN Antasari Banjarmasin. The qualitative method of case study type was chosen in this study. Researchers conducted interviews, observations, and documentation to obtain valid and accurate data. The results of the study indicate that hybrid learning management in growing student motivation in higher education is carried out through; analysis of the readiness of human resources in universities; providing a hybrid learning platform to support learning programs; Learning design that combines online and offline (face-to-face) learning, and ongoing evaluation of hybrid learning.